Improving Community Economy Through Innovation in Soft Ice Cream Machine and Food Dehydrator Technology and the Development of Local Wisdom in Sambibulu Village - Marwiyah, Siti; Hartati, Fadjar Kurnia; Suryawati, Cicilia Tantri; Tampubolon, Liosten Rianna Roosida Ully; Kurniawati, Ony (Pascasarjana Universitas Mataram, 2025)
Empowering Assisted Villages with the title